A MODEL HOW TO CREATE SOCIAL VALUE ADDED FOR COMPANY IN INDONESIA - Maharani Rahma (Dinasti International Journal of Education Management And Social Science, 2020)
The purpose of establishing a company can be divided into two, economic goals and social goals. Economic goals regarding the company's efforts to maintain it’s existence, the company's social goals are expected to meet the desires of investors, employees, providers of factors of production and the wider community. Both of these goals support one another, the company will not be able to realize its social goals if the company has not been able to achieve the company's economic goals. Social Value Added (SVA) which is an adaptation of Economic Value Added (EVA) is one of the tools to assess a company's performance to achieve social goals. The positive SVA shows that the social influence created by the company has yielded results in excess of the capital costs that must be incurred, which will later be proven by obtaining "social profitability". SVA is in line with what scientific progress. is saying that perceptions about company value have changed. which at first a company was judged by its ability to generate profits, but a good company is a company that is able to produce high profitability and high social responsibility as well. Corporate social responsibility (CSR) is intended to create harmony between the interests of the company's management and the interests of its stakeholders. Corporate social responsibility is one of the strategic plans implemented by organizations with regard to suitainable social which companies consider their involvement in social activities, and also decrease the destructive effects of business on society and the natural environment. In Indonesia, corporate social responsibility is no longer voluntary. The company is responsible for holding company activities accountable, but now it is mandatory for some companies to implement them. This is regulated in Act Number 40 of 2007 concerning Limited Liability Companies (UU PT), which was passed on July 20, 2007. Based on this, As a novelty, we need a model to evaluate the social responsibility that has been done in order to generate social profit for the company. as well as being a model of how companies can achieve Social Value Added.